The Principal’s Role as an Innovator in Advancing School Digitalization through the Implementation of a Digital Library Program at SDN Tambakrejo 01 Semarang - Lilik Muslichati; Nur Khoiri; Lilik Ariyanto (Jurnal Penelitian Pendidikan IPA, 2025)
SDN Tambakrejo 01 Semarang, under the leadership of the Principal, is known to have faced serious challenges, such as the impact of flooding that damaged facilities and physical book collections. This innovation not only overcomes logistical challenges but also changes the literacy culture in the school. This study uses a qualitative case study design that aims to describe and interpret the role of the principal as an innovator in developing a digital library program at SDN Tambakrejo 01 Semarang. Starting from this reality, this study aims to explore the role of the principal as an innovator in the development and implementation of school digitalization through a digital library program at SDN Tambakrejo 01 Semarang. The results of this study The Principal of SDN Tambakrejo 01 initiated the Digital Library program after reflecting on two main problems: book damage due to flooding and low student literacy scores (around 50). An innovative solution resulting from joint reflection by teachers and parents was the creation of the Digital Reading Corner (Subadi) application and the One Student One Book (SASI SABU) program, where students create and upload their own digital books. This program is implemented routinely using available resources (Chromebooks) and supported by close collaboration from all parties, successfully increasing student literacy scores from 50 to 87 in one year, and its sustainability is maintained through regular evaluations and annual competitions.